Combination of the MEK inhibitor pimasertib with BTK or PI3K-delta inhibitors is active in preclinical models of aggressive lymphomas. (8th March 2016) - Gaudio, E.; Tarantelli, C.; Kwee, I.; Barassi, C.; Bernasconi, E.; Rinaldi, A.; Ponzoni, M.; Cascione, L.; Targa, A.; Stathis, A.; Goodstal, S.; Zucca, E.; et al.
Abstract : The B-cell receptor with its downstream signaling pathways is an important therapeutic target for B-cell lymphomas. Here, we present preclinical evidences of the synergism of combining the MEK1/2 inhibitor pimasertib with the BTK inhibitor ibrutinib or with the PI3K-delta inhibitor idelalisib, providing the rational for clinical trials exploring these combinations in patients with lymphomas. Abstract: Background: Lymphomas are among the most common human cancers and represent the cause of death for still too many patients. The B-cell receptor with its downstream signaling pathways represents an important therapeutic target for B-cell lymphomas. Here, we evaluated the activity of the MEK1/2 inhibitor pimasertib as single agent and in combination with other targeted drugs in lymphoma preclinical models. Materials and methods: Cell lines derived mature B-cell lymphomas were exposed to increasing doses of pimasertib alone. Immunoblotting and gene expression profiling were performed. Combination of pimasertib with idelalisib or ibrutinib was assessed. Results: Pimasertib as single agent exerted a dose-dependent antitumor activity across a panel of 23 lymphoma cell lines, although at concentrations higher than reported for solid tumors. Strong synergism was observed with pimasertib combined with the PI3K inhibitor idelalisib and the BTK inhibitor ibrutinib in cell lines derived from diffuse large B-cell lymphoma (DLBCL) and mantle cell lymphoma. The data were confirmed in an in vivo experiment treating DLBCL xenografts with pimasertib and ibrutinib. Conclusion: The data presented here provide the basis for further investigation of regimens including pimasertib in relapsed and refractory lymphomas.